Childfree dalam Perkawinan Perspektif Hak Asasi Manusia dan Maqashid Asy-Syari’ah Hifdz An-Nasl - Ragil Friedenta Pantow; Shofiyun Nahidloh (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The purpose of this study is to collaborate the phenomenon of Childfree in the midst of modern society and how the perspective of Human Rights and Maqashid Ash-Sharia Hifdz An-Nasl in responding to this phenomenon. Childfree shows a cultural sign that allows marriage but supports not having children. Although Indonesia has a relatively high birth rate, problems with globalization, economic difficulties, and foreign cultures lead to certain people's beliefs that marriage does not have to have children. This research uses qualitative research to describe reality systematically with accurate preparation. The results showed that there are differences of opinion regarding the phenomenon of childfree, Human Rights Perspectives Every person or couple has a personal right to decide when and how many children they want, including the choice to become childfree. No other person or entity shall prohibit this right. And the perspective of Maqashid Ash-Sharia Hifdz An-Nasl safeguards offspring (Hifdzun nasl), as Allah Almighty commands his people, through marriage that seeks to follow the sunnah of the Prophet and abstain from adultery. This is mentioned in Q.S. An-Nisa verse 3. Thus, having offspring in Islam is a recommendation. Remembering that every married couple has the right to choose not to have children.